2022
DOI: 10.1007/s00380-022-02118-8
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of extracellular matrix biomarkers predicts the development of impaired systolic function within 1 year of acute myocardial infarction

Abstract: The clinical utility of combining extracellular matrix (ECM) biomarkers to predict the development of impaired systolic function following acute myocardial infarction (AMI) remains largely undetermined. A combination of ELISA and multiplexing assays were performed to measure matrix metalloproteinase (MMP)-2, MMP-3, MMP-8, MMP-9, periostin, N-terminal type I procollagen (PINP) and tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) in plasma samples from 120 AMI patients. All patients had an echocardiogram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…45,46 The activation of MMP-9 is associated with poorer prognosis in patients with AMI. 47,48 In addition, therapy with MMP-9 signaling pathway as a target might be a promising option for the treatment of AMI. 49 Our results revealed that the mRNA level of MMP-9 increased in AMI, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 The activation of MMP-9 is associated with poorer prognosis in patients with AMI. 47,48 In addition, therapy with MMP-9 signaling pathway as a target might be a promising option for the treatment of AMI. 49 Our results revealed that the mRNA level of MMP-9 increased in AMI, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%